Globalisation and Air Transportation Industry: A Case Study of Malaysia - Kamaruddin, Shahrul Kamal (2010)
Air transportation remains a large and growing industry that is central to the globalisation process. The globalisation impact on the air transportation industry remains largely focused on the airlines, while the impact on airports is rarely defined. The objective of this research is to identify the processes of globalisation that impact the air transportation industry specifically on airport development and operations that will greatly influence the changing nature of airports. A survey questionnaire and an interview within the case study framework on Malaysia Airports Holdings Berhad (MAHB) were undertaken. A total of 36 MAHB staff participated in the interview that covers questions on policies of the organisation in the globalised environment and more importantly, their views on the impact that globalisation has had on airports operated by MAHB. To further clarify the questionnaire findings, an interview was undertaken with the organisation’s Senior Manager, Corporate Planning. 94% of respondents agreed that globalisation has had a positive impact on MAHB, with 73% felt that business of airports has been greatly influenced by globalisation. 67% felt that such scenarios call the need for airport charges to be increased to support airport operations and expansions, while 79% felt that the new Low Cost Carrier Terminal (LCCT) building was necessary. The results reflected the high level of confidence of the organisation’s employees that MAHB as the company has benefitted from globalisation and that MAHB is in a position to face the challenges of globalisation. The findings of this research can be an addition to the scarce literatures on the impact of globalisation on airports. To a certain extent, the findings can be a source of material for airport operators in adapting to the changes in air transportation industry brought about by globalisation. The impact of globalisation on airports may be different for a developing nation and developed as globalisation affects each country differently.